2022
DOI: 10.3390/ijms23094845
|View full text |Cite
|
Sign up to set email alerts
|

Identification, In Silico Characterization, and Differential Expression Profiles of Carotenoid, Xanthophyll, Apocarotenoid Biosynthetic Pathways Genes, and Analysis of Carotenoid and Xanthophyll Accumulation in Heracleum moellendorffii Hance

Abstract: Heracleum moellendorffii Hance is a non-woody forest plant widely used in China, Korea, and Japan because of its various therapeutic properties. However, the genetic details of the carotenoid pathway (CP), xanthophyll pathway (XP), and apocarotenoid pathway (AP) genes have not been studied. Thus, the CP, XP, and AP genes of H. moellendorffii were detected and analyzed. A total of fifteen genes were identified, of which eight, four, and three belonged to CP, XP, and AP, respectively. All identified genes posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The extract was dried and resuspended in 50:50 ( v / v ) dichloromethane/methanol. HPLC analysis was performed according to the method described by Sathasivam et al [ 79 , 80 ] ( Figure S4 ). The carotenoid contents were calculated according to the HPLC peak areas compared to the internal standard calibration curves.…”
Section: Methodsmentioning
confidence: 99%
“…The extract was dried and resuspended in 50:50 ( v / v ) dichloromethane/methanol. HPLC analysis was performed according to the method described by Sathasivam et al [ 79 , 80 ] ( Figure S4 ). The carotenoid contents were calculated according to the HPLC peak areas compared to the internal standard calibration curves.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few GLVs investigated in the present study were previously explored for carotenoid composition and content. Sathasivam et al [ 40 ] also recorded the dominance of lutein and β-carotene in Heracleum moellendorffii leaves, with a total carotenoid content of 1668 µg/g dry weight (DW). In Pimpinella brachycarpa, Yoon et al [ 51 ] recorded 54.5 and 32.3 µg/g FW of lutein and β-carotene, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…GLVs have abundant phytopigments. Several studies have confirmed the content of α-carotene, β-carotene, lutein, violaxanthin, zeaxanthin, and α-tocopherol in a few traditional GLVs [ 15 , 16 , 36 , 37 , 38 , 39 , 40 ]. However, data on carotenoid content and compositions of several traditional GLVs consumed in Korea are still unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Three papers have demonstrated a strong interest in the study of the genomes of plants and their association with some important traits. Sathasivam et al (2022) [ 19 ] discussed the expression mechanism of the carotenoid pathway in Heracleum moellendorffii Hance and analyzed the expression distribution of related genes in different organs, enabling the investigation of strategies that could enhance the anti-carcinogenic properties of H. moellendorffii . Kim et al (2023) [ 20 ] proposed a combined approach based on single-nucleotide polymorphism (SNP) array and GWAS analyses and unraveled the genetic basis of complex root traits in soybean, which will provide valuable clues for further genetic research and the breeding of climate-adaptable soybeans with improved root traits.…”
mentioning
confidence: 99%